THE EFFECT OF STORY COMPLETION TECHNIQUE ON STUDENTS’ SPEAKING ABILITY (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The objective of this study is to determine the effect of the Story Completion Technique on the Students’ Speaking Ability. The research design uses a Quasi Experimental Design; None Equivalent Control Group. The place and time of this study will be conducted at SMK Nurul Gina Abidin, Kasomalang in the second semester of the academic year 2021/2022 from January to March 2022. The sample of this research is the X TKJ (Teknik Komputer Jaringan) class students as the Experiment group with 25 students and X TKR (Teknik Kendaraan Ringan) as the Control Group with 25 students. The sampling technique will use purposive sampling. In collecting data, researchers will conduct pretest in Experiment Class and Control Class. Then, the researcher will give Treatment. In Experiment Class, researcher will use the Story Completion technique. Students make a circle while a teacher in a center of circle. Teacher begins telling stories, students continue to make a good story one by one. The control class will only use conventional teaching method. Posttest will give after the researcher carried treatments, it will know the different results between Experiment and Control classes. The instruments of this research are the syllabus, lesson plans, and tests. The primary data collection techniques in this research are pretest and posttest. Data analysis of this research is used SPSS. This Technique assume can effective to the students’ speaking ability.
Keywords: Story Completion Technique; Speaking